Evaluating Friction Dampers for Seismic Protection of Non-structural Elements in Hospitals - Yusril Abdurrahman; Ari Wibowo; Achfas Zacoeb (The Indonesian Institute of Science and Technology Research, 2026)
This study evaluates the effectiveness of friction dampers in improving the seismic performance of non-structural components in hospital buildings. A five-story reinforced concrete hospital, intentionally modeled to exceed allowable drift limits, was analyzed using nonlinear time history analysis under three earthquake scenarios: BSE-1E (225-year), BSE-2E (975-year), and BSE-2N (2475-year), assuming soft soil conditions. Non-structural components were classified as drift- or acceleration-sensitive, with damage probabilities assessed using fragility curves and categorized into risk classes. Results show that friction dampers significantly reduced damage probability for acceleration-sensitive components up to 74% for cabinet contents under BSE-1E. However, drift-sensitive elements remained vulnerable, particularly in higher-intensity events, due to the building's flexible design and limited damper activation. While friction dampers improved global structural performance, their effectiveness declined with increasing seismic demand. These findings underscore the potential and limitations of friction dampers in retrofitting hospital buildings and highlight the need for careful damper sizing and consideration of alternative strategies to protect non-structural systems.